ANALYSIS OF THE EFFECT OF WEBSITE SERVICE QUALITY AND TRUST ON USER SATISFACTION WITH WEBQUAL METHOD IN E-COMMERCE INDONESIA - Tubagus Achmadi; Miftah Andriansyah (International Journal Science and Technology, 2022)
This study aims to analyze the quality of the Shopee and Lazada Indonesia websites which have been measured using the Webqual method. To find out in the midst of the COVID-19 outbreak like this, whether many people are switching to online shopping or are still loyal to shopping directly at the market, and users' trust in making non-cash payments. The research methodology used is a qualitative approach. The sample used is people from any circle who have made purchases at Shopee or Lazada at least 1 time as many as 100 respondents. The data collection instrument used primary data. Primary data was obtained by using a questionnaire distributed through social media. Analysis of the data used in this study were normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, f test and t test with the help of SPSS version 22. By showing the Asymp value. Sig (2-tailed) shows 0.200. Because the value of Asymp. Sig (2-tailed) > 0.050 this means that the residual data is normally distributed so that the data can be accepted. The VIF value of X1 and X2 is less than 10 and the tolerance value is more than 0.10. So, it can be concluded that in the regression model there is no multicollinearity. The scatterplot graph shows that the points spread randomly and are spread both above and below zero on the Y axis, there is no heteroscedasticity. The constant of 10.215 states that if the independent variables, namely website quality and trust, are considered constant. H1 is accepted, namely the quality of the website has a significant positive effect on user satisfaction, this can be seen in the significance value of 0.003 or p value <0.05.